Design, Synthesis, and Surface Modification of Materials Based on Transition‐Metal Dichalcogenides for Biomedical Applications. Issue 12 (20th November 2017) - Zhu, Shuang; Gong, Linji; Xie, Jiani; Gu, Zhanjun; Zhao, Yuliang
Abstract: With the rapid development of nanotechnology, the emerging transition‐metal dichalcogenides (TMDCs) have become one of the most promising inorganic nanomaterials for medical applications due to their distinctive structures and properties. TMDCs with different sizes and morphologies exhibit unique structural advantages, as well as versatile properties. However, concerning their practicability for biomedical applications, routes toward their synthesis and chemical/physical functionalization for biosystem applications must be identified. Herein, recent advances in the design, synthesis, and surface modification of TMDC‐based nanomaterials specific for biomedical applications are reviewed. First, the basic consideration regarding how to fabricate biocompatible TMDCs efficiently for biomedical use is discussed. Solution‐based synthesis methods for 2D TMDCs, as well as TMDC‐based nanocomposites are then summarized. In addition, general strategies applied for surface functionalization of TMDCs are also discussed. Finally, current challenges and future perspectives for these promising materials in biosystem applications are outlined. Abstract : The design, synthesis, and functionalization of transition‐metal dichalcogenide (TMDC)‐based nanomaterials specific for biomedical applications are discussed. The basic considerations of how to fabricate TMDCs efficiently for biomedical use, and the strategies for solution‐based synthesis and surface modification of TMDCs in biological applications are summarized. Current challenges and future perspectives for these promising materials for application in biosystems are outlined.